Elastic Stable Intramedullary Nail: The viable technique for pediatric long bone fixation - Osateerakun, MD, Phatcharapa; Limpaphayom, MD, Noppachart (Journal of Southeast Asian Orthopaedics, 2022)
Treatment options for a pediatric diaphyseal fracture have been debated for a long time. Cast immobilization is used as a nonsurgical treatment to avoid risks from operations. However, casting has disadvantages such as shortening or angulation of the fracture site, difficulty in nursing care, and a delay in the return to school. Internal fixation has been indicated for some patients who cannot encounter those drawbacks. Elastic stable intramedullary nailing (ESIN) is one of the fixations of choice. Rational, surgical techniques and possible complications of ESIN are reviewed in this article. Benefits from this treatment system are that it is a minimally invasive procedure, the promotion of callus formation, easier nursing care, and early ambulation. There are some complications from this technique which were proposed as minor and major complications. Soft tissue irritation around the entry point of the nail is the most common minor complication whereas unacceptable angulation has the highest incidence among major complications.